STUDENTS’ NEED ON TASK BASED LANGUAGE TEACHING WORKSHEET AT SMPN 2 TIGO LURAH BASED ON GENDER - Suci Azani Putri (State Institute of Islamic Studies Batusangkar, 2021)
This study aims to investigate students’ needs on task based language worksheet at SMPN 2 Tigo Lurah based on gender differences. This type of research was research and development research. This research targets are the seven grade students of SMPN 2 Tigo Lurah. To achieve this purpose, questionnaires and document analysis were conducted to collect the data. Data were then analyzed descriptively. Based on the need analysis result, it found that students need task based language teaching worksheet to learn English. The students need the pre-tasks task, the input of tasks and all materials stated in the curriculum. However, the differences are on the responses of the male and the female students. The female students gave high responses on the needs of task based language teaching responses than male students. Hence, the students need task based language teaching worksheet so that task based language teaching worksheet can be developed and used in the classroom.